Dimensions of Service Quality Satisfaction Community at the Village Government Office - Setyobakti, Moh. Hudi; Murniati, Wahyuning (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
Enhancement public service is one goal of the village setting for the community. Therefore, this study analyzed the correlation between the dimensions of customer satisfaction and community satisfaction. The sample in this study was 83 respondents, Lumajang community who use the services of the village offices, which were analyzed using multiple linear regression. The results showed empathy variables that influence people's satisfaction significantly. The coefficient of determination in this study was 77.8%, it can do that only requires empathy Lumajang community village government in the ministry. But the village government should not rule out other dimensions of quality of service, because they have laws that regulate their work to the public.